A study on patients requiring emergency hemodialysis in Hospital Universiti Sains Malaysia - Rosedee, Noor Aida (2020)
Objective: It is currently unknown whether there are differences in patients' characteristics and hemodialysis (HD) outcomes between patients who undergo emergent HD in the emergency department (ED) and non-ED setting (i.e. ward, intensive care unit (ICU) or HD unit). Therefore, this study aims to compare the clinical and non-clinical characteristics and HD outcomes between patients who underwent emergent HD at ED (“ED group”) and non-ED (“non-ED group”) settings. Methods: This is a retrospective observational study among patients admitted through the ED of a tertiary teaching hospital in Malaysia and underwent acute HD within 24 hours of admission between January 2016 till December 2017. Results: A total of 177 patients were included in the study. The bivariable analysis found that the ED group had a significantly higher proportion of new cases (i.e. no known history of HD), fluid overload cases, and refractory fluid overload indication as compared to the non-ED group. It was also found that the ED group had a higher proportion of those requiring mechanical ventilation and 60-day mortality. Hierarchical regression found that HD locations play a significant role in determining HD outcomes in terms of 60-days mortality and ICU stays. Those who underwent HD at non-ED have 0.263 (95%CI=0.096, 0.723) times lower odds of 60-day mortality but 2.946 (95%CI=1.051, 8.258) times higher odds of staying in ICU. Conclusion: There were significant differences in patients’ characteristics and HD outcomes between patients underwent HD in ED and non-ED settings. Emergent HD location may influence 60-day mortality and ICU stays. As the current study is insufficient to confidently justify the use of HD in ED settings as compared to the non-ED setting, a randomized controlled trial is needed.